The Influence of Tofu Pulp Flour Substitution on Protein Content and Acceptability Level of Chicken Nugget - Dayu Putri, V; Nita, Y (KnE Life Sciences, 2019)
This research has been carried out at the Food and Beverage Laboratory of UPT of Testing and Goods Quality Certification (PSMB) of Riau Province from April to September 2018. The purpose of this research was to determine the influence of tofu pulp flour substitution on protein content and determine the panelist acceptability level of chicken nugget produced. The research design used was a Complete Random Design (CRD) with 4 treatments of tofu pulp flour substitution which were 0%, 10%, 20% and 30% with two replications. Protein content was analyzed by Kjedahl method and panelist acceptability level used organoleptic test. Analysis of protein content data was carried out by using the One Way Anova test and level of acceptability used the Kruskal-Wallis test with a level of 5%, respectively. The research result of protein content analysis showed that there was no significant influence of tofu pulp flour substitution on protein content (p 0.116 > 0.05). Organoleptic test result obtained the most preferred chicken nugget was substitution of 10% tofu pulp flour. Data analysis showed no significant difference between the aroma and the texture of chicken nugget produced (p > 0.05). Meanwhile an analysis of the chicken nugget taste showed there was a significant difference (p < 0.05) between the two groups of tofu pulp flour, so that the analysis continued with the Man-Whitney test and the result of the group that had a difference in taste was between the tofu pulp flour substitution group with 0% and 30% and between groups which tofu pulp flour substitution of 10% and 30%. Based on the research results, it can be concluded that tofu pulp flour can be used as a substitution in chicken nugget processing without reducing its nutritional value. Keywords: tofu pulp flour, chicken nugget, protein content, organoleptic test